The formation and stripping mechanism of oxide film on stainless steel surfaces - Zhenqi Shen; Guangkai Wang; Fang Bao; Tianhao Liu; Yang Fei; Zhenni Xie; Yuxin Liang; Xincheng Wang (International Journal of Advanced Nuclear Reactor Design and Technology)
Typically, equipment in nuclear facilities operating in nitric acid media are made of stainless steel. Retired equipment exhibits relatively high levels of radioactivity, and chemical cleaning is a cost-effective and efficient method for decontamination. Currently, the formation rules of oxide films on stainless steel surfaces during long-term immersion in nitric acid systems, leading to the development of strong oxidizing chemical decontamination agents, were investigated. It was found that oxide film of stainless steel immersed in nitric acid solution for about 150 days stabilized at a thickness of around 6 μm. Subsequently, an inorganic acid-based strong oxidizing decontamination agent was developed with nitric acid as the main component. Meanwhile, two distinguished additives (A and B) were developed to promote the stripping of oxide film. The optimized ingredients were 3.3 mol/L nitric acid, 5 wt% additive A, and 0.12 wt% additive B, which resulted in a removal thickness of up to 27.35 μm immersed at 30 °C for 10 min. Furthermore, the stripping mechanism of oxide films on stainless steel surfaces was proposed, revealing the transition from a passivated state to an over-passivated state in nitric acid environments and leading to intergranular corrosion and potential grain detachment.